An α-hemoglobin-derived peptide (m)VD-hemopressin (α) promotes NREM sleep via the CB1 cannabinoid receptor - Xie, Jun-Fan; Wang, Lin-Xin; Ren, Wen-Ting; Wang, Can; Gao, Jin-Xian; Chen, Hai-Lin; Zhao, Xue-Qi; Ren, Yan-Li; Xie, Yu-Ping; Shao, Yu-Feng; Hou, Yi-Ping (Frontiers in Pharmacology, 2023)
Hemopressin and related peptides have shown to function as the endogenous ligands or the regulator of cannabinoid receptors. The previous studies demonstrated that the endocannabinoid system played important roles in modulating several physiological functions such as sleep, olfaction, emotion, learning and memory, and reward behaviors. Mouse VD-hemopressin (α) [(m)VD-HPα], an 11-residue peptide derived from the α1 chain of hemoglobin, was recently presumed as a selective agonist of the CB1 receptor. The present study was undertaken to investigate the effects of (m)VD-HPα on the sleep–wake cycle and power spectrum of cortical EEG in freely moving rats and the potential neurons in the brain activated by (m)VD-HPα. The results showed that 20.1 nmol of (m)VD-HPα i.c.v. administration increased non-rapid eye movement (NREM) sleep in the first 2 h section accompanied by an increase in EEG delta (0.5–4 Hz) activity. The (m)VD-HPα-induced NREM sleep enhancement was due to extended episode duration instead of the episode number. In addition, the effect of (m)VD-HPα (20.1 nmol) on sleep–wake states was significantly attenuated by an antagonist of the CB1 receptor, AM251 (20 nmol, i.c.v.) but not by the CB2 receptor antagonist, AM630 (20 nmol, i.c.v.). In comparison with vehicle, (m)VD-HPα increased Fos-immunoreactive (-ir) neurons in the ventrolateral preoptic nucleus (VLPO), but reduced Fos-ir neurons in the lateral hypothalamus (LH), tuberomammillary nucleus (TMN), and locus coeruleus (LC). These findings suggest that (m)VD-HPα promotes NREM sleep via the CB1 cannabinoid receptor to probably activate VLPO GABAergic neurons, but inactivates the LH orexinergic, LC noradrenergic, and TMN histaminergic neurons.